2022
DOI: 10.1037/edu0000703
|View full text |Cite
|
Sign up to set email alerts
|

Does instructional quality mediate the link between teachers’ emotional exhaustion and student outcomes? A large-scale study using teacher and student reports.

Abstract: A negative association between symptoms of teacher burnout (e.g., emotional exhaustion) and students' academic outcomes has been demonstrated in previous research. Although, in theoretical models, it has been suggested that this association can be explained through changes in teachers' instructional behavior, these mediating processes have not yet been empirically tested. Therefore, in the present study, we examined (a) whether teachers' emotional exhaustion is related to students' self-concept, interest, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 87 publications
(169 reference statements)
0
27
0
5
Order By: Relevance
“…Our finding that principals and teachers who reported more health concerns also had higher emotional exhaustion indicated that individuals' health is a central life domain and one of the most important resources ( Maybery et al, 2007 ). Previous research also showed that daily worries about individuals' health and/or symptoms of health impairment were significantly related to increased emotional exhaustion ( Klusmann et al, 2022 ; Mather et al, 2014 ). Since the time of data collection for the present study, hygiene measures and vaccinations have reduced the risk of infection.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our finding that principals and teachers who reported more health concerns also had higher emotional exhaustion indicated that individuals' health is a central life domain and one of the most important resources ( Maybery et al, 2007 ). Previous research also showed that daily worries about individuals' health and/or symptoms of health impairment were significantly related to increased emotional exhaustion ( Klusmann et al, 2022 ; Mather et al, 2014 ). Since the time of data collection for the present study, hygiene measures and vaccinations have reduced the risk of infection.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the majority of teachers and principals reported increases in emotional exhaustion and experienced the pandemic as harmful. This is especially alarming considering the association of teachers’ burnout with health, retention in the profession, the quality of their instruction, and student outcomes ( Arens & Morin, 2016 ; Klusmann et al, 2016 ; Klusmann et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers with higher levels of job exhaustion also tend to display lower job satisfaction and higher turnover intention (Delali et al, 2020 ; Lee et al, 2019 ; Mudau, 2016 ). Moreover, teachers’ job exhaustion is also associated with students' compromised individual and educational outcomes, such as negative self-concept, diminished learning interest, poor academic achievement, and low school satisfaction (Arens & Morin, 2016 ; Klusmann et al, 2022 ). Thus, it is critical to systematically examine the etiology of teachers’ job exhaustion.…”
Section: Conceptualization Theoretical Framework and Empirical Evidencementioning
confidence: 99%